Coordination complexes and polymers from the initial application of phenyl-2-pyridyl ketone azine in mercury chemistry. (8th January 2015) - Khandar, Ali Akbar; Ghosh, Barindra Kumar; Lampropoulos, Christos; Gargari, Masoumeh Servati; Yilmaz, Veysel T.; Bhar, Kishalay; Hosseini-Yazdi, Seyed Abolfazl; Cain, John M.; Mahmoudi, Ghodrat
Abstract : Graphical abstract: The initial use of phenyl-2-pyridyl ketone azine in mercury chemistry afforded a series of neutral monomeric and dimeric Hg II coordination compounds and polymers. The synthesis of different products is dependent upon the identity of the ancillary ligands present in the reaction mixture, namely halides and pseudo-halides. All products were characterized using X-ray crystallography, thermal analyses, and fluorescence studies. Abstract: A series of new mercury(II) azine Schiff base complexes have been synthesized and characterized from the initial use of phenyl-2-pyridyl ketone azine in Hg II chemistry. The synthetic/crystallization technique utilized involved the use of a branched tube, where temperature differential allowed for the slow crystallization of the products. The synthesized compounds are the mononuclear [Hg(L)Cl2 ] (1 ), [Hg(L)Br2 ] (2 ), [Hg(L)(NO2 )2 ] (3 ), and the dinuclear [Hg2 (μ-L)(SCN)4 ] (4 ) coordination compounds, as well as a 1D coordination polymer [Hg(L)(μ-I)2 HgI2 ] n (5 ) (L = phenyl-2-pyridyl ketone azine). From the X-ray data, it is evident that this versatile ligand functions as a bi- or tridentate chelate, and is also able to bridge two Hg II centers. The crystal structures of1 and2 are similar, both containing two crystallographically independent Hg II molecules, one tetrahedrally coordinated and one exhibiting trigonal bipyramidal geometry. The heptacoordinated Hg II center in3 adopts a distorted capped trigonal prismatic coordination sphere, while in the dinuclear complex4, the metal ions are bridged via the bis(bidentate) L and each center is also bound to two S-bonded thiocyanate units. The one-dimensional coordination polymer in5 consists of a tetrahedral HgI4 and a trigonal bipyramidal HgN3 I2 chromophore unit, bridged by μ-I − bridges. The thermal stability of the crystal lattice in1 –5 follows the pattern3  > 1  > 2  > 5  > 4, as studied by TG/DTA, while the TG data of1, 2, and5 are similar, but different than the respective ones for3 and4, between which important similarities are observed. In the solid state, the ligand and compounds1 –5 exhibit intraligand π → π ∗ fluorescence at room temperature.